Toward the development of methodology for designing helicopter flight control laws by integrating handling qualities requirements - Antonioli, J.C.; Taghizad, A.; Rakotomamonjy, T.; Ouladsine, M. (My University, 2014)
Piloting a helicopter is a demanding task for human operators: autopilots have been introduced by manufacturers to assist pilots in their piloting task. Designing the gains of the associated control laws – taking into account Handling Qualities requirements from standards such as the ADS-33 – is a difficult industrial problem. NASA has already led many studies on this area. These works have led to the development of CONDUIT© (Control Designer’s Unified Interface), a computer aided design tool for rotary and fixed wing aircrafts control laws using interactive optimization techniques. The tool has demonstrated its benefits in terms of time of development reduction. ONERA has been working for several years to the establishment of another process. One of the first ideas was to lead local sensitivity studies, and use the results as design guidance. Then these results have been confronted with some analytical developments led on simplified models. This paper shows how these analytical studies can be used to initialize the gain tuning process efficiently, taking into account the structure of the system and the requirements from handling qualities standards (ADS-33). A tool has been developed: it generates charts of Flying Qualities. Thanks to the charts generated for each case of study, the gains of the control laws can be efficiently initialized for the simplified models, with Flying Qualities objectives. The expected results are compared with those obtained with the full linear model. Sensitivities can then be used to help in designing more precisely the gains. Finally, full nonlinear simulations are led in order to compare the results with the expected Flying Qualities. As a conclusion, all these studies seem to lead to a full and efficient process of gain tuning taking into account the constraints from the control law structures and the requirements from the handling qualities standard. Furthermore, the procedure can be applied from the very first stage of tuning: the initialization of the gains.